Borings in early Eocene turtle shell from the Wasatch Formation, South Pass, Wyoming. (29th March 2016) - Zonneveld, John-Paul; Bartels, William S.; Gunnell, Gregg F.; McHugh, Luke P.
Abstract: Borings in fossil turtle shells collected from the lowermost beds of the early Eocene Cathedral Bluffs Tongue of the Wasatch Formation in the northwestern part of the Green River Basin near South Pass, Wyoming, are herein described. Individual turtle shells in the study area are characterized by as few as one or two and as many as >100 borings. The borings include both non-penetrative forms (those which do not pass fully though the shell) as well as penetrative forms (those which pass fully from the exterior to the interior surface of the shell). All non-penetrative forms occur on external surfaces of the carapace and plastron (i.e. those that would have been accessible while the host taxon was alive). Two new ichnogenera and four new ichnospecies are established to describe these borings. Karethraichnus (new ichnogenus) includes three ichnospecies: K . lakkos (new ichnospecies), K . kulindros (new ichnospecies), and K . fiale (new ichnospecies). Karethraichnus lakkos are shallow (non-penetrating), hemispherical pits with rounded, to flattened bases. Karethraichnus kulindros are deep, non-penetrative traces with a cylindrical profile, an axis approximately perpendicular to the substrate surface and with rounded to flattened, hemispherical termini. Karethraichnus fiale are penetrative traces with a cylindrical to bi-convex or flask-shaped profile, and an axis approximately perpendicular to the substrate surface. Thatchtelithichnus (new ichnogenus) Thatchtelithichnus holmani (new ichnospecies) consist of non-penetrative borings into a bone substrate. They consist of a ring-shaped trace, with a central pedestal or platform. The position of the borings on the shells, and evidence of syn-emplacement healing of the borings in several of the turtles, indicates that these borings were emplacement by ectoparasites/mesoparasites while the animals were living. Similar traces in modern emydid turtles are attributed to ticks, leeches, or spirorchid liver flukes.